Synergistic application of melatonin and silicon oxide nanoparticles modulates reactive oxygen species generation and the antioxidant defense system: a strategy for cadmium tolerance in rice - Faisal, Mohammad; Faizan, Mohammad; Soysal, Sipan; Alatar, Abdulrahman A. (Frontiers in Plant Science, 2024)
Unfavorable environmental conditions pose a major barrier to sustainable agriculture. Among the various innovative strategies developed to protect plants from abiotic stress, the use of phytohormones and nanoparticles as “stress mitigators” has emerged as one of the most important and promising approaches. The objective of this study was to observe the protective role of melatonin (Mel) and silicon oxide nanoparticles (SiO-NPs) in rice (Oryza sativa L.) seedlings under cadmium (Cd) stress. Rice seedlings have reduced growth and phytochemical attributes when grown in Cd-contaminated (0.8 mM) pots. Seedlings under Cd stress had 38% less shoot length (SL), 53% total soluble sugar (TSS) and 57% protein content. However, superoxide dismutase (SOD), hydrogen peroxide (H2O2) and malondialdehyde (MDA) increased by 51%, 37% and 34%, respectively, under Cd stress. Beside this, activities such as peroxidase (POX) also elevated in the plants subjected with Cd-stress. In contrast, Mel (100 µm) as foliar spray and SiO-NPs (100 mg/L) as root dipping reduced oxidative stress in rice seedlings under Cd stress by reducing reactive oxygen species (ROS) generation. Furthermore, the application of Mel and/or SiO-NPs significantly increased the activity of antioxidative enzymes that scavenge ROS. The combined application of SiO-NPs and Mel increased growth, gas exchange and photosynthetic attributes, chlorophyll value, and protein content. It causes alleviation in the activity of SOD, CAT and POX by 73%, 62% and 65%, respectively. Overall, this study findings show that Mel and/or SiO-NPs can potentially protect the rice crop against oxidative damage under Cd stress.